ESP8266 Internet of Things cookbook : over 50 recipes to help you master the ESP8266's functionality - Schwartz, Marco (Packt Publishing, 2017)
Exploring the low cost WiFi module About This Book Leverage the ESP8266's on-board processing and storage capability Get hand- on experience of working on the ESP8266 Arduino Core and its various libraries A practical and enticing recipe-based book that will teach you how to make your environment smart using the ESP8266 Who This Book Is For This book is targeted at IOT enthusiasts who are well versed with electronics concepts and have a very basic familiarity with the ESP8266. Some experience with programming will be an advantage. What You Will Learn Measure data from a digital temperature and humidity sensor using the ESP8266 Explore advanced ESP8266 functionalities Control devices from anywhere in the world using MicroPython Troubleshoot issues with cloud data monitoring Tweet data from the Arduino board Build a cloud-connected power-switch with the ESP8266 Create an ESP8266 robot controlled from the cloud In Detail The ESP8266 Wi-Fi Module is a self contained System on Chip (SOC) with an integrated TCP/IP protocol stack and can give any microcontroller access to your Wi-Fi network. It is capable of either hosting an application or offloading all Wi-Fi networking functions from another application processor. This book contains practical recipes that will help you master all ESP8266 functionalities. You will start by configuring and customizing the chip in line with your requirements. Then you will focus on core topics such as on-board processing, sensors, GPIOs, programming, networking, integration with external components, and so on. We will also teach you how to leverage Arduino using the ESP8266 and you'll learn about its libraries, file system, OTA updates, and so on. The book also provide recipes on web servers, testing, connecting with the cloud, and troubleshooting techniques. Programming aspects include MicroPython and how to leverage it to get started with the ESP8266. Towards the end, we will use these concepts and create an interesting project (IOT). By the end of the book, readers will be proficient enough to use the ESP8266 board efficiently. Style and approach This recipe-based book will teach you to build projects using the ESP8266.